Actualización del sistema SCADA para el control y análisis de indicadores de operación del invernadero N°1 del Campus Salache. - Chango Sánchez, Bryan Alexander (2021)
Ecuador's agricultural sector has not been exploited to its full potential, due to the fact that its cultivation method is still mostly conventional, delaying the progress of this important sector. The problem lies in the fact that there is not enough technology in the greenhouses to optimize the processes, improve the quality of the products and increase the production of this sector. The objective of the research was to analyze the scope of updating the SCADA system for the monitoring and control of the variables of greenhouse N°1 of the Salache campus, which is developed specifically for the benefit of students and teachers of agronomic engineering, since by remotely monitoring the variables of humidity and temperature, the correct operation of the greenhouse could be verified and its performance was checked by obtaining a data base. The monitoring and control were carried out through the graphic interface of the WinCC software, which benefited the production to be of higher quality, and also to increase the productivity indexes. A context was also developed to establish strategic objectives and implementation plans for new variables, through the study of the needs of greenhouse N°1 of the Salache campus.